Bullying and mental health of adolescents in Nepal (Journal of Patan Academy of Health Sciences, 2023)
Bullying is one of the common issues among children and adolescents, bearing significant implications on mental health and wellbeing. Although there are few studies, there remains a gap in the synthesized understanding of bullying and its link to the mental health of Nepalese adolescents. Hence, this narrative review has examined the literature centering on the prevalence and impact of bullying within the context of Nepalese adolescents. Although there was limited number of relevant articles, the findings from the review revealed that bullying is a widespread experience among Nepalese adolescents and is associated with several mental health challenges such as anxiety, depression, and tendencies towards self-harm and suicidal behavior. The review sheds light on the importance of addressing bullying in order to prevent psychological consequences and foster the mental health of adolescents in Nepal.